Britain, Australia and the bomb the nuclear tests and their aftermath - Arnold, Lorna; Smith, Mark (Palgrave Macmillan, 2006)
Britain, Australia and the Bomb tells the story of the unique partnership between the two countries to develop nuclear weapons in the 1940s and 1950s. This new edition includes fresh evidence about the weapons under development, the effects of the tests on participants, and the recent clean-up of the testing range.